Persepsi Guru Bahasa Inggris Terhadap Kemampuan Diri dalam Implementasi Pembelajaran Berdiferensiasi - Della Hanifah Nurbaeti; Sri Setyarini (Loquen, 2024)
Differentiated learning is one of the emphasized aspects of the Merdeka Curriculum. However, in reality, teachers face several challenges in implementing differentiated learning. Some literature mentions that not all schools using the Merdeka Curriculum implement differentiated learning. This is due to various obstacles, including inadequate facilities and teachers' insufficient abilities. This study found that the perceptions of English teachers at the secondary level in Bandung regarding their ability to implement differentiated learning are categorized as good. However, teachers still face difficulties in designing assessments and evaluations that align with the principles of differentiated learning. Nevertheless, teachers are most confident in their ability to understand students' characteristics and learning needs.